Traitement Des Phosphates Naturels De Tahoua (Niger) Par Quelques Acides Conventionnels - Ousmane Mahamane Sani; Zanguina Adamou; Natatou Ibrahim (European Scientific Journal, ESJ, 2017)
Within the framework of upgrading natural phosphate of Tahoua, a study was carried out on the dissolution of ore by inorganic acid (sulfuric acid, nitric acid) and organic acid (citric acid) solutions according to pH and attack time. The obtained results show a sudden drop of dissolution rate at pH above 2 and a dissolution almost zero beyond pH 4. The kinetic study shows fast dissolution of ore one hour after the attack. However, this dissolution is slow beyond one hour with few dissolved phosphorus during a relatively high period of time. Furthermore, the sulfuric acid solutions dissolve the ore better than those of citric and nitric acid: 41.07%; 37.03% and 35.64% of dissolved phosphorus respectively for sulfuric, citric and nitric acid solutions at the concentration of 1mol/L.